Clonal dissemination of an NDM-2-producing Acinetobacter baumannii ST103 clone resulting in an outbreak in an intensive care unit of a Lebanese tertiary care hospital - Tania Nawfal Dagher; Linda Hadjadj; Fadi Bittar; Fadi Fenianos; Elias Abdo; Jean-Marc Rolain; Charbel Al-Bayssari (Journal of Global Antimicrobial Resistance)
Objective: Multidrug-resistant bacteria, including carbapenem-resistant Acinetobacter baumannii (CRAB), are considered a major public health threat, particularly those which are responsible for nosocomial infections. This study aimed to investigate the molecular mechanism of carbapenem resistance and the clonal relationship of CRAB isolates of a probable outbreak in the intensive care unit (ICU) of Saydet Zgharta University Medical Center, in north Lebanon. Methods: Thirty-two non-duplicate CRAB isolates were collected from patients hospitalised in the ICU. Antibiotic susceptibility testing was carried out using the disk diffusion method and carbapenemase-encoding genes were searched for using standard polymerase chain reaction. Epidemiological relatedness was studied using multilocus sequence typing. Results: Polymerase chain reaction and multilocus sequence typing results suggested the presence of two different periods: period 1 (November 2018 to February 2019), where 15 CRAB isolates were collected harbouring the blaOXA-23 and blaOXA-24 genes mainly and belonging to several clones; and period 2 (March to May 2019), considered an outbreak period where 17 carbapenem-resistant isolates were isolated, harbouring mostly the blaNDM-2 gene, never previously described in Lebanon and belonging to ST103. Infection control measures implemented in Saydet Zgharta University Medical Center successfully eradicated the NDM-2-producing CRAB ST103 clone, thus putting an end to this outbreak in the ICU department. Conclusions: This study showed that infection control measures and adequate identification of NDM-producing A. baumannii remain a powerful tool to limit the spread of such resistant micro-organisms.